Radiation-Induced Degradation of Pirimiphos Methyl in Aerated Solution - Hendig Winarno; Agustin N; M. Bagyo; Winarti A. Lindu; Ermin K. Winarno (PPIKSN-BATAN, 2004)
Degradation of pirimiphos methyl (1) as an active ingredient in Minawet insecticide 250 EC formulation in aqueous solution was studied. The absorbance, pH, COD (Chemical Oxygen Demand) in aerated solution, and the analyses of degradation products at various irradiation doses with dose rate of 5 kGy/h were observed. The absorbance decreased rapidly at low doses (£ 10 kGy), while at high doses (> 10 kGy) decreased slowly. The optimum irradiation dose for pirimiphos methyl degradation in aerated solution was found to be 15 kGy at pH 3.6. At that condition, more than 99% of pirimiphos methyl has been degraded and the COD of solution decreased about 82%. The analysis of irradiated samples by GC-MS and HPLC showed that 2-diethylamino-6-methyl-4-oxo-3,4-dihydropyrimidine (3) and oxalic acid were clarified as degraded products